ENTH and ANTH domain proteins participate in AP2-independent clathrin-mediated endocytosis - Manna, Paul T.; Gadelha, Catarina; Puttick, Amy E.; Field, Mark C. (The Company of Biologists, 2015)
Clathrin-mediated endocytosis (CME) is a major route of entry into eukaryotic cells. A core of evolutionarily ancient genes encodes many components of this system but much of our mechanistic understanding of CME is derived from a phylogenetically narrow sampling of a few model organisms. In the parasite Trypanosoma brucei, which is distantly related to the better characterised animals and fungi, exceptionally fast endocytic turnover aids its evasion of the host immune system. Although clathrin is absolutely essential for this process, the adaptor protein complex 2 (AP2) has been secondarily lost, suggesting mechanistic divergence. Here, we characterise two phosphoinositide-binding monomeric clathrin adaptors, T. brucei (Tb)EpsinR and TbCALM, which in trypanosomes are represented by single genes, unlike the expansions present in animals and fungi. Depletion of these gene products reveals essential, but partially redundant, activities in CME. Ultrastructural analysis of TbCALM and TbEpsinR double-knockdown cells demonstrated severe defects to clathrin-coated pit formation and morphology associated with a dramatic inhibition of endocytosis. Depletion of TbCALM alone, however, produced a distinct lysosomal segregation phenotype, indicating an additional non-redundant role for this protein. Therefore, TbEpsinR and TbCALM represent ancient phosphoinositide-binding proteins with distinct and vital roles in AP2-independent endocytosis.